The autonomic nervous system as a therapeutic target in heart failure: a scientific position statement from the Translational Research Committee of the Heart Failure Association of the European Society of Cardiology. (26th September 2017) - van Bilsen, Marc; Patel, Hitesh C.; Bauersachs, Johann; Böhm, Michael; Borggrefe, Martin; Brutsaert, Dirk; Coats, Andrew J.S.; de Boer, Rudolf A.; de Keulenaer, Gilles W.; Filippatos, Gerasimos S.; Floras, John; Grassi, Guido; et al.
Abstract : Despite improvements in medical therapy and device‐based treatment, heart failure (HF) continues to impose enormous burdens on patients and health care systems worldwide. Alterations in autonomic nervous system (ANS) activity contribute to cardiac disease progression, and the recent development of invasive techniques and electrical stimulation devices has opened new avenues for specific targeting of the sympathetic and parasympathetic branches of the ANS. The Heart Failure Association of the European Society of Cardiology recently organized an expert workshop which brought together clinicians, trialists and basic scientists to discuss the ANS as a therapeutic target in HF. The questions addressed were: (i) What are the abnormalities of ANS in HF patients? (ii) What methods are available to measure autonomic dysfunction? (iii) What therapeutic interventions are available to target the ANS in patients with HF, and what are their specific strengths and weaknesses? (iv) What have we learned from previous ANS trials? (v) How should we proceed in the future?